Analysis of Cloud Computing Characteristics, Services and Security Against Information Technology Strategy for Small Medium Enterprises - Dheva Sari Silaban; Sardjoeni Moedjiono (Return : Study of Management, Economic and Bussines, 2024)
Along with the development of the economy and technology, especially in cloud computing in Indonesia, Small and Medium Enterprises (SME) services also take part in this development. Cloud computing is an information technology innovation that allows users to use resources based on demanding utilities. Limited capital, human resources, and access to marketing networks are no longer a problem for SME businesses significant because of the benefits of Cloud Computing. Based on partial testing, the results of this study indicate there is no influence and insignificance of cloud computing security on variables characteristic variables of cloud computing. Similarly, the security variable has no influence and insignificant on the adoption of the strategy variable. While service variables have a positive and significant effect on security variables.